2021
DOI: 10.34172/jlms.2021.53
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Photobiomodulation Therapy in Different Doses on Bone Repair of Critical Size Defects in Rats: A Histomorphometric Study

Abstract: Introduction: Photobiomodulation therapy (PBM) appears to induce osteogenesis and stimulate fracture repair; because of its capacity, it is considered a promising treatment, but the characteristics of response to different radiation doses must be investigated through in vivo studies to establish their safety and effectiveness. Thus, this paper aims to analyze the effects of the PBM at different doses on the repair of critical bone defects through histological and histomorphometric analyses. Methods: Sixty 90-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
1
10
0
2
Order By: Relevance
“…The increasing bone formation observed over time in this research was also reported in studies that used similar methodologies [ 20 , 44 ]. These data demonstrate that PBM may have positive effects on bone tissue, improving the quality and density of newly formed bone [ 44 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The increasing bone formation observed over time in this research was also reported in studies that used similar methodologies [ 20 , 44 ]. These data demonstrate that PBM may have positive effects on bone tissue, improving the quality and density of newly formed bone [ 44 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 97%
“…The histological data also showed positive effects regarding the combination of treatment methods in the bone regeneration process, which was already visible at 14 postoperative days. In this period of analysis, it is possible to observe the presence of vascular sprouts in the G4/BFB + PBM group, which may be due to the effects of PBM therapy on the local microcirculation [ 46 ]. In addition to PBM, the fibrin biopolymer also contributed to stimulate angiogenic factors and neovascularization, as observed in previous studies [ 20 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…With the gradual exploration of PBM, many researchers have investigated the role of PBM in osteoblasts and found that PBM can significantly facilitate multiplication of MC3T3-E1 cells [ 29 ]. De Marco et al suggested that PBM could improve fracture healing in rats and promote bone regeneration in bone defects [ 30 ]. Other studies have suggested that different wavelengths of PBM have significant regulatory effects on osteoblast differentiation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, innovative modalities, such as low-intensity pulsed ultrasound, photobiomodulation therapy (PBMT) with low-level laser, and hyperbaric oxygen therapy, or their combination, are being evaluated in an attempt to improve metabolism and accelerate the bone repair process [ 19 , 20 , 21 , 22 ]. Photobiomodulation has been shown to be capable of biostimulation of bone cells during in vitro or in vivo studies [ 23 , 24 , 25 ]. The most accepted hypothesis in relation to the mechanism of action is that monochromatic laser photons activate chromophores in the cell’s cytochrome C oxidase, resulting in accelerated cellular activity, increased ATP and alkaline phosphatase (ALP) concentrations, and calcium release [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Photobiomodulation has been shown to be capable of biostimulation of bone cells during in vitro or in vivo studies [ 23 , 24 , 25 ]. The most accepted hypothesis in relation to the mechanism of action is that monochromatic laser photons activate chromophores in the cell’s cytochrome C oxidase, resulting in accelerated cellular activity, increased ATP and alkaline phosphatase (ALP) concentrations, and calcium release [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%